Assessments of 14 Exploited Fish and Invertebrate Stocks in Chinese Waters Using the LBB Method - Liang, Cui; Xian, Weiwei; Liu, Shude; Pauly, Daniel (Frontiers in Marine Science, 2020)
Due to lLimited by data availability, only a small subset of the exploited fish and invertebrate populations have been assessed along Chinese coastsal waters, which precludes comprehensive management of the fisheries. Here, we applied a length-based Bayesian biomass estimator (LBB) to 14 fish and invertebrate stocks in China’s coastal waters to estimate their growth, length at first capture and current relative biomass (B/B0, B/BMSY) from length-frequency (LF) data. Of the 14 populations assessed, 1 have collapsed, 9 are grossly over-exploited, and 3 are overfished. Moreover, 13 populations have smaller mean lengths at first capture (Lc) than the optimal length at first capture (Lc_opt), indicating that they are suffering from growth overfishing. Thus, larger mesh sizes in commercial fishery would increase both the catch and biomass for these species, given current levels of fishing mortality. Our results confirm that fishery resources in China’s coastal waters are strongly depleted, and that stricter management measures are needed to restore the abundance of China’s marine fisheries resources.